Teamwork and Competency : Drivers of Lecturers’ Work-Quality in Banten, Indonesia - Apriani, Reni; Hanafie, Syadeli; Anriani, Nurul (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the effect of team work, communication competence and competency on the lecturersâ€™ work quality. The research approach was quantitative and the analysis method used was path analysis. The research instrument consisted of a structured survey questionnaire developed based on the operational definitions of the key variables, to measure the specified constructs. The research was conducted at Universitas La Tansa Mashiro (UNILAM), Banten using survey with the samples of 93 lecturers being selected randomly. The research findings showed that: (1) team work has positively and significantly affected the work quality; (2) competency has positively and significantly affected the work quality; (3) team work has positively and significantly affected the competency; (4) communication competence has positively and significantly affected the competency. Based on these findings, it can be concluded that enhancing the work quality of lecturer can be done through strengthening team work and competency.Â It was also obtained that work quality was not significantly influenced by communication competence, which implied that the direct effect of communication competence on the work quality was not supported by empirical data in this research.